b KOLONIALISME DAN TRANSFORMASI HUKUM ISLAM DI INDONESIA: DARI MASA PENJAJAHAN HINGGA ERA GLOBALISASI - Linda, Fitra Syari; Sari, Anastyapatika (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract: Through discriminatory practices like customary law and the notion of receptie, European colonialism has undermined Indonesia's native legal system, especially Islamic law, since the 16th century. This essay looks at how colonialism affected Islamic law and how it evolved in the postcolonial and globalization eras. The findings demonstrate how laws like the Juvenile Criminal Justice System Law and the Sharia Banking Law helped to codify Islamic law after World War II.  However, Islamic law was only applicable in private settings during the colonial era. Fatwas themselves are dynamic, acting as a tool for social change in addition to resolving theological concerns. This study demonstrates that legal dualism is a detrimental legacy of colonialism. But it also made it possible for Islamic law to be incorporated back into the national legal framework.  According to the Pancasila model, cooperation between academics, policymakers, and religious experts can incorporate Islamic law to make it applicable, relevant, and helpful in the development of a more complete national legal system. Keywords: Colonialism, Islamic Law, Fatwa